Sensitive LC-MS/MS Method for the Simultaneous Determination of Bisoprolol and Triamterene in human plasma - G, Hemavathi; M, Hipparagi S (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: A highly sensitive, specific, and rapid liquid chromatography-electrospray ionization-mass spectrometry (MS)/MS method has been developed and validated for the simultaneous quantification of bisoprolol and triamterene in human plasma using metoprolol as an internal standard (IS) as per regulatory guidelines. Methods: Both the analytes and IS were extracted from plasma using a protein precipitation extraction method. Chromatography was achieved on Welchrom XB C18, 50 mm×4.6 mm, 5 µm column using an isocratic mobile phase (2 mM ammonium formate acetonitrile, 70:30 v/v) at a flow rate of 0.60 ml/minute. Results: The total chromatographic run time was 3.5 minute and the elution of bisoprolol, triamterene, and IS occurred at ~2.57, 1.30 and 1.57 minute, respectively. A linear response function was established at 2.04-210 ng/ml for both the analytes in human plasma. The intra- and inter-day accuracy and precisions were in the range of 1.12-7.87 and 1.26-6.36%; 1.46-6.13 and 1.65-7.34% for bisoprolol and triamterene, respectively. Conclusion: A new robust method was developed for simultaneous determination of Bisoprolol and Triamterene in human plasma. The method was strictly validated according to the ICH [1] guidelines. The information thus obtained from the study can be used for the full pharmacokinetic profiling in individuals. Keywords: Bisoprolol, Triamterene, Liquid chromatography-mass spectrometry/mass spectrometry, Method validation, Human plasma, Pharmacokinetics.